Gadolinium Doping Enhances the Photoacoustic Signal of Synthetic Melanin Nanoparticles: A Dual Modality Contrast Agent for Stem Cell Imaging - Lemaster, Jeanne E. (Chem Mater, 2018)
In this paper, we show that gadolinium-loaded synthetic melanin nanoparticles (Gd(III)-SMNPs) exhibit up to a 40-fold enhanced photoacoustic signal intensity relative to synthetic melanin alone and higher than other metal-chelated SMNPs. This property makes these materials useful as dual labeling agents because Gd(III)-SMNPs also behave as magnetic resonance imaging (MRI) contrast agents. As a proof-of-concept, we used these nanoparticles to label human mesenchymal stem cells. Cellular uptake was confirmed with bright-field optical and transmission electron microscopy. The Gd(III)-SMNP-labeled stem cells continued to express the stem cell surface markers CD73, CD90, and CD105 and proliferate. The labeled stem cells were subsequently injected intramyocardially in mice, and the tissue was observed by photoacoustic and MR imaging. We found that the photoacoustic signal increased as the cell number increased (R(2) = 0.96), indicating that such an approach could be employed to discriminate between stem cell populations with a limit of detection of 2.3 × 10(4) cells in in vitro tests. This multimodal photoacoustic/MRI approach combines the excellent temporal resolution of photoacoustics with the anatomic resolution of MRI.